The Waldenses in the new world - Watts, George B. (Duke University publications, 1941)
Waldo and his followers, or the poor men of Lyons -- Refugees on Staten Island and the Delaware River -- Manakin-Town, Virginia -- Colonies in Georgia and South Carolina -- Mormons and the Waldenses -- South American Colonies -- Monett, Missouri -- Wolf Ridge, Texas -- Valdese, North Carolina -- Waldenses in New York City -- Individuals and smaller groups -- American co-operation -- Music and literature.